Frailty and medication adherence among older adult patients with hypertension: a moderated mediation model - Wang, Anshi; Wan, Jingjing; Zhu, Lijun; Chang, Weiwei; Wen, Liying; Tao, Xiubin; Jin, Yuelong (Frontiers in Public Health, 2023)
Objective Medication adherence has a critical impact on the well-being of older adult patients with hypertension. As such, the current study aimed to investigate the mediating role of health literacy between frailty and medication adherence and the moderating role of educational level. Methods This cross-sectional study included patients admitted to the geriatric unit of a hospital. Participants were interviewed using the four-item Morisky Medication Adherence Scale, the Frailty Phenotype Scale, and the Health Literacy Management Scale. Spearman’s correlation coefficients were used to assess the association between variables. Mediation and moderated mediation analyses were performed using Process version 4.1 via Model 4 and 14, respectively. Results Data from 388 participants were analyzed. The median (IQR [P25–P75]) score for medication adherence was 4.00 (2.00–4.00). Results revealed that after controlling for age, sex, hypertension complication(s) and body mass index, frailty significantly contributed to medication adherence (βtotal −0.236 [95% confidence interval (CI) −0.333 to −0.140]). Medication adherence was influenced by frailty (βdirect −0.192 [95% CI −0.284 to −0.099]) both directly and indirectly through health literacy (βindirect −0.044 [95% CI −0.077 to −0.014]). Educational level moderated the pathway mediated by health literacy; more specifically, the conditional indirect effect between frailty and medication adherence was significant among older adult hypertensive patients with low, intermediate, and high educational levels (effect −0.052 [95% CI −0.092 to −0.106]; effect −0.041 [95% CI −0.071 to −0.012]; effect −0.026 [95% CI −0.051 to −0.006]). The relationship between frailty and medication adherence in older adult patients with hypertension was found to have mediating and moderating effects. Conclusion A moderated mediation model was proposed to investigate the effect of frailty on medication adherence. It was effective in strengthening medication adherence by improving health literacy and reducing frailty. More attention needs to be devoted to older adult patients with hypertension and low educational levels.